The “Art of Commerce”: An Outline of Commercial Education in Twentieth-century Greece - Chatziioannou, Maria Christina; Tsilaga, Flora (The Historical Review/La Revue Historique, 2015)
The first half of the twentieth century in Greece was marked by consecutive military and civil conflicts that caused profound territorial, demographic and social changes. The movement of vast numbers of young peasants from rural areas to the capital coincided with the broadening of internal trade, a proliferation of industrial investments and the intense urbanization of Athens and other Greek cities, especially during the interwar period. This article examines education concerning the “art of commerce”, a more flexible type of training in comparison with its strictly technical equivalent; a form of education that was associated with a completely different outlook compared to the traditional apprenticeship guilds of the nineteenth century. In this context, the essay seeks to emphasize the ways in which a professional group, recognized by the state through its own associations, was specifically created and developed and how this group envisaged creating the sole educational opportunity for its own members, those working in the field of retail.